2009
DOI: 10.1007/s10822-009-9315-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dipeptidylcarboxypeptidase of Leishmania donovani: a molecular model for structure based design of antileishmanials

Abstract: Leishmania donovani dipeptidylcarboxypeptidsae (LdDCP), an angiotensin converting enzyme (ACE) related metallopeptidase has been identified and characterized as a putative drug target for antileishmanial chemotherapy. The kinetic parameters for LdDCP with substrate, Hip-His-Leu were determined as, Km, 4 mM and Vmax, 1.173 micromole/ml/min. Inhibition studies revealed that known ACE inhibitors (captopril and bradykinin potentiating peptide; BPP1) were weak inhibitors for LdDCP as compared to human testicular AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Figure 3E depicts the docking of d ‐captopril in active site of homology model of LdDCP. As observed earlier (17), d ‐captopril may chelate to zinc atom via carboxylate oxygen. In this preferred mode of binding, carbonyl group of captopril can interact with hydroxyl group of Tyr604.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…Figure 3E depicts the docking of d ‐captopril in active site of homology model of LdDCP. As observed earlier (17), d ‐captopril may chelate to zinc atom via carboxylate oxygen. In this preferred mode of binding, carbonyl group of captopril can interact with hydroxyl group of Tyr604.…”
Section: Resultssupporting
confidence: 71%
“…Captopril, an ACE‐specific inhibitor was able to inhibit significantly LdDCP enzyme activity and the parasite growth which strongly suggests that this newly identified DCP could serve as drug target in Leishmania . The 3D structural model for LdDCP has already been constructed using the X‐ray crystal structure of DCP from E. coli as template (17). Captopril docking with hACE, LdDCP, and EcDCP and analysis of molecular electrostatic potentials suggested that the active site domain of these three enzymes has several minor but potentially important structural differences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations